2007
DOI: 10.1002/ijc.22706
|View full text |Cite
|
Sign up to set email alerts
|

Frequent inactivation of SPARC by promoter hypermethylation in colon cancers

Abstract: Epigenetic modification of gene expression plays an important role in the development of human cancers. The inactivation of SPARC through CpG island methylation was studied in colon cancers using oligonucleotide microarray analysis and methylation specific PCR (MSP). Gene expression of 7 colon cancer cell lines was evaluated before and after treatment with the demethylating agent 5-aza-2 0 -deoxycytidine (5Aza-dC) by oligonucleotide microarray analysis. Expression of SPARC was further examined in colon cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 33 publications
9
90
1
2
Order By: Relevance
“…This finding differs from a recent study by Yang et al (2007), where only partial methylation (and no hypermethylation) was observed in their cases of colorectal cancers within a shorter 221 bp region of the SPARC promoter (Yang et al, 2007). One possible explanation to account for this difference between our studies may be in the processing of the clinical samples: all of the samples used in the current study were laser capture microdissected to minimise potential contamination of either normal colonic epithelium in our colorectal cancer specimens, and vice versa.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding differs from a recent study by Yang et al (2007), where only partial methylation (and no hypermethylation) was observed in their cases of colorectal cancers within a shorter 221 bp region of the SPARC promoter (Yang et al, 2007). One possible explanation to account for this difference between our studies may be in the processing of the clinical samples: all of the samples used in the current study were laser capture microdissected to minimise potential contamination of either normal colonic epithelium in our colorectal cancer specimens, and vice versa.…”
Section: Discussioncontrasting
confidence: 99%
“…Aberrant hypermethylation of the SPARC promoter has also been observed in cancers of the lung (Suzuki et al, 2005), prostate (Wang et al, 2005), endometrium (Rodriguez-Jimenez et al, 2007) and leukaemia cell lines (DiMartino et al, 2006). Recent studies using genome-wide screening to identify genes that are targeted for aberrant methylation in tumours have also consistently shown SPARC expression to be inducible by 5-Aza-2 0 deoxycytidine, in pancreatic (Sato et al, 2003), cervical (Sova et al, 2006), and colorectal cancer cell lines (Yang et al, 2007). In this study, we found an overall methylation pattern of 60% in the SPARC promoter of primary colorectal cancer specimens, while only 28% of the CpG sites were partially methylated.…”
Section: Discussionmentioning
confidence: 97%
“…This is also supported from animal models were SPARC deficiency strongly suppressed adenoma formation in the intestine in Sparc knockout mice intercrossed with Apc(Min/ þ ) mice. 39 In contrast, a significant association of SPARC methylation and poorer prognosis was reported by Yang et al 40 Although the authors analyzed a large cohort of patients, they did not differentiate between tumor stages nor did they consider stratification by chemotherapy. In our study, SPARC promoter methylation tended to be associated with shortened overall survival and disease-free survival, only in patients who received chemotherapy.…”
Section: Modern Pathology (2014) 27 906-915mentioning
confidence: 96%
“…[7][8][9][10][11][12] In colorectal cancer (CRC), the role of SPARC is not well understood. 13,14 SPARC is expressed not only by cancer cells but also by stromal cells surrounding the tumor. 5 Tumor-associated stromal cells such as cancer-associated fibroblasts are important components of the tumor microenvironment, where their interaction with cancer cells leads to the production of regulatory growth factors…”
Section: Introductionmentioning
confidence: 99%